Development of line follower ir mobile robot with obstacle remover [electronic resource] - 404989 Muhamed Abdul Fatah Muhamed Mukhtar (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2007